2020
DOI: 10.1101/2020.03.06.980888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the minimum sampling design for population genomic and microsatellite studies. An analysis based on wild maize

Abstract: 14Massive parallel sequencing is revolutionizing the field of molecular ecology by allowing to 15 understand better the evolutionary history of populations and species, and to detect genomic 16 regions that could be under selection. However, the needed economic and computational 17 resources generate a tradeoff between the amount of loci that can be obtained and the number 18 of populations or individuals that can be sequenced. In this work, we analyzed and compared 19 two extensive genomic and one large micro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Since SMC++ uses both AFS distributions and linkage between loci to infer past effective population size, the software is well suited for population genomic studies in comparison with other implementations that rely on deep sequencing of fewer individuals. Generally, a minimum of 8 individuals should be used in population studies for estimation of the AFS and genetic diversity derived parameters from high-density genetic markers such as SNP data from resequencing (71,72). Here 19 coastal cod and 22 offshore cod were used to infer past effective population sizes, which should provide sufficient power and precision for the utilized approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Since SMC++ uses both AFS distributions and linkage between loci to infer past effective population size, the software is well suited for population genomic studies in comparison with other implementations that rely on deep sequencing of fewer individuals. Generally, a minimum of 8 individuals should be used in population studies for estimation of the AFS and genetic diversity derived parameters from high-density genetic markers such as SNP data from resequencing (71,72). Here 19 coastal cod and 22 offshore cod were used to infer past effective population sizes, which should provide sufficient power and precision for the utilized approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic structure could potentially mirror the F ST significance we observed in our study. Although, these values and their level of significance could be biased by the low number of genetic markers and individuals involved in their analyses (e.g., Aguirre‐Liguori et al, 2020; Ruzzante, 1998). The genetic structure observed across Madagascar by Ratrimomanarivo et al (2009) could also result, as suggested by the authors, in a sampling bias (i.e., unsampled areas between genetically differentiated populations).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, neutral molecular markers, such as microsatellites allow for a wide variety of robust analyses (Selkoe and Toonen, 2006; Guichoux et al, 2011; Kalia et al, 2011) including the inference of demographics and migration processes. Microsatellites can be used for many relevant analyses; however, recent studies have highlighted the importance of using a high number of loci (>20) with a comprehensive geographic representation of the species (including numerous populations and individuals) for making reliable conclusions (Aguirre‐Liguori et al, 2020).…”
mentioning
confidence: 99%